Two new bamboo feeding leafhopper species of the subfamily Deltocephalinae (Hemiptera: Cicadellidae) from China - Huang, Yihong; Tang, Liuhong; Huang, Yingying; Webb, Michael D.; Duan, Yani (Zootaxa, 2025)
Two new bamboo feeding leafhopper species of the subfamily Deltocephalinae, from China, are described and illustrated: Bambusananus anhuiensis Huang & Tang, sp. nov. (Athysanini) and Scaphotettix aurantiacus Huang & Tang, sp. nov. (Mukariini). Checklists to the two tribes and two genera from China are given and keys to the species of the two genera are provided.